Pengaruh NPL, CAR, dan BI Rate terhadap ROA pada Bank Badan Usaha Milik Negara - Helmalia Fauziah (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The research is use to looking for how strong the influence of Non Performing Loan (NPL),Capital Adequacy Ratio (CAR) as internal bank factor and BI Rate as bank external factors on Return on Assets (ROA) at state-owned enterprise bank. The population used is state-owned banks whose financial reports have been published to Bank Indonesia from 2010-2018. For sampling using random sampling obtained 4 state-owned banks (BTN bank, Mandiri bank, BRI bank, BNI bank), while the data used is secondary data obtained from the websites of each bank and also Bank Indonesia. Multiple Regression Analysis is a method used and hypothesis testing, namely the F-test to know-simultaneously and the T-test to know-partially. The results showed that the variable Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), and BI Rate simultaneously had a significant effect on Return on Assets (ROA). Partially Non Performing Loan (NPL) has a significant negative effect on ROA, the Capital Adequacy Ratio (CAR) shows a negative and insignificant effect on ROA, while the BI Rate partially has no significant effect on Return on Assets (ROA).